2007
DOI: 10.1016/j.yjmcc.2006.09.007
|View full text |Cite
|
Sign up to set email alerts
|

CaMKII inhibition targeted to the sarcoplasmic reticulum inhibits frequency-dependent acceleration of relaxation and Ca2+ current facilitation

Abstract: Cardiac Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) in heart has been implicated in Ca 2+ current (I Ca ) facilitation, enhanced sarcoplasmic reticulum (SR) Ca2+ release and frequency dependent acceleration of relaxation (FDAR) via enhanced SR Ca 2+ uptake. However, questions remain about how CaMKII may work in these three processes. Here we tested the role of CaM-KII in these processes using transgenic mice (SR-AIP) that express four concatenated repeats of the CaMKII inhibitory peptide AIP selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
81
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 54 publications
8
81
1
1
Order By: Relevance
“…This hypothesis was supported by the effect of the specific CaMK-inhibitor AIP, which was able to substantially blunt the exercise training-induced increase in fractional shortening and Ca 2+ transient amplitude. Previous work has shown that CaMKII has a series of targets in the cell, including the L-type Ca 2+ channel, the ryanodine receptor 2 (RyR2), and SERCA-2a [8,9]. Hence, inhibiting CaMK with AIP may have limited the inotropic response of exercise by acting on a series of sites in the excitation-contraction coupling process that collectively abolished the training-induced effects.…”
Section: Aerobic Interval Training Up-regulates Serca-2a Plb and Camkmentioning
confidence: 99%
See 2 more Smart Citations
“…This hypothesis was supported by the effect of the specific CaMK-inhibitor AIP, which was able to substantially blunt the exercise training-induced increase in fractional shortening and Ca 2+ transient amplitude. Previous work has shown that CaMKII has a series of targets in the cell, including the L-type Ca 2+ channel, the ryanodine receptor 2 (RyR2), and SERCA-2a [8,9]. Hence, inhibiting CaMK with AIP may have limited the inotropic response of exercise by acting on a series of sites in the excitation-contraction coupling process that collectively abolished the training-induced effects.…”
Section: Aerobic Interval Training Up-regulates Serca-2a Plb and Camkmentioning
confidence: 99%
“…Mainly, PLB is phosphorylated by cAMP-dependent protein kinase A (PKA) at serine (Ser)-16 and by Ca 2+ /calmodulin dependent kinase II (CaMKII) at threonine (Thr)-17 [8]. There are also indications of a PLB-independent action of CaMKII upon SERCA-2a that appears to increase diastolic SR Ca 2+ re-uptake [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies, using PLB KO animals, indicated that FDAR was not dependent on PLB but rather depended on CaMKII activity. In a recent study [40] the role of CaMKII was tested using TG mice that express four concatenated repeats of the CaMKII inhibitory peptide AIP (Auto Inhibitor Peptide). These mice show a moderate reduction in cardiac function and a decreased response to β-adrenergic stimulation.…”
Section: Frequency Dependent Acceleration Of Relaxationmentioning
confidence: 99%
“…As a result of these factors, the calcium decline may critically and predominantly modulate relaxation in unloaded myocytes, and thus manipulation of calcium decline will directly affect relaxation kinetics when load is absent. Indeed, in the unloaded isolated myocyte at sub-physiological pacing frequencies, inhibition of CAMKII targeted to the SR blunts FDAR [17,40]. However, relaxation of the myocardium under loaded conditions as it occurs in vivo is likely governed in a significantly different manner.…”
Section: Role Of Myofilaments In Fdarmentioning
confidence: 99%